Biomass Utilization as Renewable Energy for Optimization of National Energy Mix - Arif Haryana (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2018)
Indonesia still relies heavily on energy derived from fossil fuels, especially petroleum and coal. The large share of fossil energy in the national energy mix can have a negative impact on national development, as it increases the dependence of national energy supplies from imports and increases in greenhouse gas emissions, carbon dioxide. The Government of Indonesia has issued a national energy policy whose goal is to achieve an optimal national energy mix, which is to reduce the share of fossil fuels and increase the use of renewable energy. Indonesia has the potential to produce abundant biomass as renewable energy and can use it to replace fossil fuels. However, the development and utilization of biomass as an energy source is still very small compared to its potential. Biomass energy development policy has begun to receive attention from the government, although it is still focused on the development and use of liquid biofuels, especially palm oil-based biodiesel. There is no clear policy to support the development and utilization of solid biomass to meet national energy needs. Meanwhile, foreign countries, Korea for example, have developed a strategy to utilize Indonesia's biomass as fuel for their power plants. As a country with huge biomass potential, it is ironic that Indonesia has not used biomass as a source of energy to support development, while other countries use it. This paper aims toprovide policy recommendations for developing biomass energy, both in terms of production capacity and demand for use in the country.